TARI JARAN GOYANG: SIMBOL PEMIKAT ASMARA - Suharti, Mamik (Acintya, 2015)
A genre of dance Jaran Goyang is one of the traditional dance genres in Banyuwangi initiated byÂ Suparman which is composed in 1960s. The treatment developing is executed by SumitroHadi, a veryÂ productive dance expert in Banyuwangi. The dance Jaran Goyang represents a form of traditionaldance with love theme. The vocabularies of dance movements, dance music as well as ricikanthat areÂ used refer to the existing traditional dance. The dance name is taken from the name of a love spellÂ called â€œjaran goyangâ€. Jaran Goyang choreography shows about love refusal of a woman butÂ finally and suddenly she falls in love due to the supernatural power of the spell jaran goyang.Keywords: dance, rarely, symbol, attractive trick, amour.